FACTORS AFFECTING THE DECISION MAKING TO CHOOSE DANCE SCHOOL IN BANGKOK METROPOLITAN AREA - Deerod, Yasita; Worapishet, Thirarut (PEOPLE: International Journal of Social Sciences, 2024)
This study investigates factors influencing the decision-making process of individuals choosing dance schools in the Bangkok Metropolitan Area. Using a mixed-methods approach, the research combines quantitative surveys and qualitative interviews to identify key determinants such as location, reputation, cost, curriculum, and instructor qualifications. Findings reveal that while cost and location are significant, the reputation of the school and instructor qualifications play crucial roles. The study aims to provide insights for dance school administrators to better understand their target market and improve their offerings. Objectives include studying the demographic characteristics of those who choose dance schools in Bangkok, examining consumer behavior toward the dance school industry, and analyzing the importance of the marketing mix (product, price, distribution channel, promotion, process, image, and presentation) for prospective students. Methods involve a quantitative approach with descriptive research and surveys. Cluster 1 is diverse in gender, with many young adults and middle-aged respondents, including students, private company officers, and lower to mid-income earners. Consumer behavior in this cluster shows a balanced interest in various dance courses, lower study expenses, a preference for evening study times, and a high preference for weekend study times. Cluster 2 is predominantly female, younger, and more diverse in occupation and income levels, with higher education levels and higher income earners. This cluster focuses on finding special skills and talents, with a strong preference for specific dance courses (especially K-pop Dance), more diverse and higher study expenses, balanced study times throughout the day, and varied main study times, including weekends and combined times. In conclusion, the importance of the marketing mix (7Ps) segments consumers into two clusters in this study.